OP0146 LONG TERM OUTCOME AND PROGNOSIS FACTORS OF ISOLATED AORTITIS. (2nd June 2020) - Ferfar, Y.; Morinet, S.; Espitia, O.; Agard, C.; Vautier, M.; Comarmond, C.; Desbois, A. C.; Domont, F.; Resche-Rigon, M.; Cacoub, P.; Biard, L.; Saadoun, D.
Abstract : Background: Aortitis is a group of disorders characterized by the inflammation of the aorta. The most common causes of aortitis are the large-vessel vasculitis i.e. giant cell arteritis (GCA) and Takayasu arteritis (TA). However, aortitis may be isolated. Because of the wide variation in the course of aortitis, predicting outcome is challenging. The optimal management strategy of isolated aortitis (IA) is still unclear as IA is poorly defined, with data consisting of small retrospective and case control studies. Objectives: To assess the long-term outcome and prognosis factors for vascular complications in patients with isolated aortitis. Methods: Retrospective multicenter study of 353 patients with non-infectious aortitis including 136 giant cell arteritis (GCA), 96 Takayasu arteritis (TA) and 73 isolated aortitis (IA). Factors associated with event-free survival, vascular event-free survival and revascularization-free survival were assessed. Risk factors for vascular complications were identified in multivariate analysis. Results: After a median follow up of 52 months, vascular complications were observed in 32.3 %, revascularization in 30 % and death in 7.6%. The 5-year cumulative incidence of vascular complications was 58% (41; 71), 20% (13; 29), and 19 % (11; 28) in IA, GCA and TA, respectively. In multivariate analysis, IA [HR, 1.85 (1.19 to 2.88), p=0.017] and male gender [1.77 (1.26 to 2.49), p<0.0001] were independently associated with vascular events. The 5-year surgery-free survival was 45% (31; 65), 71% (62; 81) and 76% (68; 86) in IA, TA and GCA, respectively. Conclusion: IA has a worse vascular prognosis than GCA and TA. Sixty percent of IA patients will experience a vascular complication within 5 years from diagnosis. Disclosure of Interests: None declared